Chemical Composition, In Vitro Antioxidant Activities, and Inhibitory Effects of the Acetylcholinesterase of Liparis nervosa (Thunb.) Lindl. Essential Oil - Jiayi Zhao; Ziyue Xu; Peizhong Gao; Xu Liu (Biomolecules, 2023)
The present study aimed to investigate the essential oil composition of Liparis nervosa (Thunb.) Lindl., grown in China, and to determine its antioxidant and inhibitory effects on acetylcholinesterase. The essential oil was obtained by hydrodistillation, and the chemical compounds were analyzed by GC-MS and GC-FID. We used 2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric reducing assay power (FRAP) to evaluate the antioxidant activity. The anti-acetylcholinesterase activity of the essential oil was also examined. Sixty-seven compounds were identified, representing 98.50 % of the total essential oil, which was shown to be rich in methyl (9E,11E)-octadeca-9,11-dienoate (31.69%), n-hexadecanoic acid (15.08%), isopropyl palmitate (12.44%), propyl tetradecanoate (7.20%), tetradecanoic acid (4.01%), 17-octadecynoic acid (3.71%), and pentacosane (2.24%). Its antioxidant ability was analyzed via ABTS (IC50 = 721.95 ± 9.93 μg/mL), DPPH scavenging capacity (IC50 > 10,000 μg/mL), and the FRAP method (Trolox equivalent antioxidant concentration 39.64 ± 3.38 μM/g). Acetylcholinesterase inhibition effects were evaluated and had an IC50 value of 51.96 ± 14.26 μg/mL. The results show that this essential oil has interesting biological potential, encouraging further investigations, especially regarding the mechanisms of action of its antioxidant and anti-acetylcholinesterase activity. This is the first time that the chemical composition, antioxidant activity, and acetylcholinesterase inhibition effects of essential oil from L. nervosa have been studied.